Jews and Muslims in South Asia: reflections on difference, religion, and race - Egorova, Yulia (Oxford University Press, 2018)
In the European imaginary Jews and Muslims have shared a common space reserved for the ultimate other and have been constructed in opposition to each other. This text examines the way Jewish and Muslim communities encounter each other in South Asia and interact in ways that do not easily fit conventional Western tropes of Jews-Muslim relations